Photographic Estimation of Roosting Density of Dusky Fruit Bat Penthetor lucasi (Chiroptera: Pteropodidae) at Wind Cave Nature Reserve, Sarawak - Mohammad Akmal Syafriq, Rushisham (Universiti Malaysia Sarawak (UNIMAS), 2015)
This study was conducted to determine the roosting density of Penthetor lucasi in Wind Cave Nature Reserve (WCNR), Sarawak. It was conducted from November 2014 to April 2015 by using photographic technique. The information on roosting density helps in estimating total population of P. lucasi by multiplying with total roosting area. A total of 75 images were analysed to estimate the roosting density. Mean roosting density was 379.9±92.2 bats/m2 on the wall while the density on the ceiling of the cave was 289.0±41.6 bats/m2. The average roosting densities were not significantly different from each other (P = 0.06). From this data, the estimation of total population of P. lucasi in the cave can be made. During the study, the populations of P. lucasi roosting inside the cave were estimated to 69919 individuals. More repeatable estimation of colony size for P. lucasi can be done by using photographic technique for monitoring activities that will help in conservation and management of the bats.